Creatinine Imprinted Photonic Crystals Hydrogel Sensor - Bushra Rafique; Rizwan Ullah Khan; Aysha Sarfraz Rizvi; Muhammad Irfan; Ghulam Murtaza; Lili Qiu; Min Xue; Zihui Meng (Arabian Journal of Chemistry, 2023)
There is a demand for simple, selective, and efficient assays for the determination of clinically important metabolites such as creatinine for healthcare. Creatinine is the by-product of muscle energy metabolism and is excreted by the kidneys. To measure creatinine in the human serum, a creatinine imprinted photonic crystal hydrogel (CIPC hydrogel) for naked-eye detection is developed. CIPC hydrogel utilizes polystyrene-based two-dimensional (2D) photonic crystal colloidal arrays (PCs-array) embedded in the polyacrylamide hydrogel containing methacrylic acid which imprinted the creatinine template. The nanocavities in the hydrogel produced after the removal of the template bind to and recognize creatinine in the serum samples. The binding is selective and specific for creatinine. The binding is observed as shrinkage of the hydrogel volume and a decrease in the particle spacing which is monitored through changes in the Debye diffraction ring diameter and a visible blue-green to blue color shift. The binding event and the mechanism are investigated by molecular dockings. The CIPC sensor demonstrates a limit of detection (LOD) of 2.45 ± 1.6 µM, a linear detection range (25–500 µM), and recovery from 85.6 % to 99.9 % in the serum samples. CIPC hydrogel is available for the rapid and quantitative onsite detection of creatinine in the human serum sample.